KAIDAH BAHASA ARAB DAN URGENSINYA TERHADAP PENAFSIRAN ALQUR’AN - Agustiar Agustiar (Jurnal An-Nur, 2015)
The Qur'an is the book of the basic sources of Islamic law, therefore, to discover the laws contained in it, is necessary for an interpretation. In interpreting the Koran there are some rules of interpretation, so that the content and messages of the Qur'an can be captured and well understood in accordance with the level of human ability. The rules of interpretation are basic principle, syar'i rules and rules of language. Linguistic rules contain a discussion of various aspects including the rules of Ism and Fi'il .In the interpretation of the Koran use Ism (noun) is a different connotation with fi’il (verb). This was caused by the differences of dilalah respectively, which implies Ism permanently and continuously without interruption (tsubut wa istimrar); fi'il otherwise similar but does not contain the word refers to an event that occurs at a specific time: past, present, and future (tajaddud wa huduts)